『尙書』 「商書」 <仲虺之誥>의 ‘慙德’에 대한 논변 - 유영옥 (동양한문학연구, 41(41), 2015)
<仲虺之誥>는 신하 중훼가 湯王의 慙德을 풀어주기 위해 放伐의 당위성을 역설하고, 나아가 大德을 더욱 日新하여 政事에 권면할 것을 경계한 글이다. 탕왕은 방벌을 끝낸 뒤 스스로 慙德하여 후세가 자신을 口實로 삼을까 두렵다고 했다. 따라서 <중훼지고>의 핵심은 바로 ‘慙德’이다. ‘慙德’에 대한 해석은 두 가지로 대별된다. 하나는 蔡沈의 『書集傳』처럼 탕왕이 桀王 방벌로 인해 참덕했다는 사실을 인정하는 견해고, 다른 하나는 茶山 丁若鏞처럼 탕왕의 참덕 자체를 부정하는 견해다. 전자는 탕왕이 堯舜의 禪讓을 뒤이어 放伐했기에 不安한 마음이 있어 자신의 德이 옛날과 같지 못함을 부끄러워했는데, 탕왕이 慙德한 이유는 응당 ‘君臣之分’을 돌아보았기 때문이라 하였다. 이는 『논어』의 ‘盡美未盡善’과 『맹자』의 ‘湯武 反之’에 대한 朱子의 思惟와 맥락이 동일하다. 후자는 <중훼지고>가 古文尙書에만 있음을 내세워 慙德과 口實을 僞作으로 보았고, 放伐한 湯武와 授受한 堯舜은 同德이니 탕왕이 부끄러웠을 리가 없다는 논리를 펼쳤다. 또 臣伐君之事의 처음은 黃帝요 탕왕이 아니며, 黃帝는 물론 탕왕도 방벌에 대한 부끄러움은 없었다고 주장하였다. After conquering and expelling tyrant King Jie, King Tang was ashamed of himself and said he was afraid to be taken a sort of pretext(gusil:口實) by descendents. To relive king Tang from the shame, his subject Zhong-hui wrote <Junghwye Jigo> that stressed it was legitimate to have cracked down on King Jie. The key point of the writings lies in ‘chamdeok’(慙德) which means ‘feeling shame about one’s degree of virtuousness’ Concerning King Tang’s chamdeok, there are two main views. One recognizes Tang’s chamdeok as a reality like Cai-shen did in 『Seojipjeon』. And the other considers it as a fake like Jeong Yak-yong did. According to the former view, King Tang conquered and expelled King Jie after abdication of the throne from both Yao and Shun, so he was ashamed that he was less virtuous than before. Thus, Tang’s chamdeok was fundamentally because the fact that he as a subject got away with the tyrant Son of Heaven reminded him of how the relations of sovereign and subject should be(君臣之分). This view complies with Confucius’saying ‘Wu is extremely beautiful, but not extremely good’(盡美未盡善) and Meng-zi’s saying ‘Both Tang and Wu are men who restored human nature of their own’(湯武 反之). While, the latter view regarded ‘chamdeok’ and ‘gusil’ as all fake since is found only in ancient literature Sangseo(古文尙書). It also insisted that Tang and Wu could never be ashamed of having conquered and expelled the tyrant king because both of them were virtuous as much as both Yao and Shun. Furthermore, that interpretation suggested King Tang shouldn’t be blamed since it was Huang-di who had been the first subject to get away with sovereign. KCI Citation Count: 1